A Modelling Approach for Integrated Planning of Port Capacity- Trade-Offs in Rotterdam Investment Planning - Dekker, Sander; Verhaeghe, Robert (Promet - Traffic&Transportation, 2006)
This paper presents a modelling approach for planning ofport capacity. The approach integrates port commercial andpublic interests. It further incorporates route competition andautonomous demand growth. It is applied to port expansion,which can be considered as a strategy for an individual port todeal with route competition. The basis for solving this planningproblem comprises an analysis of port demand and supply in apartial equilibrium model. With such an approach, the reactionof a single port on the change in a transport network comprisingalternative routes to a hinterland destination can be simulated.To establish the optimal expansion strategy, port expansion iscombined with congestion pricing. This is used for the simultaneousdetermination of 1) optimal expansion size, and 2) investmentrecovery period. The modelling approach will be appliedto Rotterdam port focusing on port expansion by means ofland reclamation. The scenmio of the entry of a new competingroute via the Italian port Gioia Tauro is used to address sometrade-offs in Rotterdam investment planning.